Characterization of sleep-wake patterns in crew members under a short-duration spaceflight. Issue 3 (2nd April 2020) - Chen, Hailong; Lv, Ke; Ji, Guohua; Liu, Zhizhen; Guo, Jinhu; Wan, Yumin; Wang, Linjie; Li, Zhili; Li, Yinghui; Qu, Lina
ABSTRACT: Sleep loss is one of large challenges during space missions. A variety of sleep problems have been shown in space. We aimed to further characterize more representative and consecutive sleep-wake patterns and to investigate sleep-wake cycle on heart rate during short duration spaceflight mission. Here, we evaluated sleep quality using Pittsburgh Sleep Quality Index, analyzed sleep time, sleep efficiency, and periods of sleep-wake rhythm via the activity data from Actiwatch, and evaluated heart rate data via the Actiheart in three crew members before, during and after a 15-day spaceflight. The study showed that the sleep quality before and during the flight were lower than that after the space flight. Crew members slept less during spaceflight relative to on Earth. The mean sleep duration during spaceflight was 6.5 ± 1.3 h, but after flight, it was 7.2 ± 1.2 h, and the sleep efficiency was significantly higher during the flight than that on Earth. The periods of sleep-wake rhythm could keep at 23.92 h during flight mission. Moreover, the heart rate decreased during spaceflight and it was more obvious during wakeful state than during sleep. These data could help us better understand the effects of short-duration spaceflight on sleep pattern.